Multiphase Flow in Oil and Gas Well Drilling - Sun, Baojiang (John Wiley & Sons, 2016)
A major contribution to the state-of-the-art for those interested in multiphase flow in well-bore, drilling cutting, hydrate and/or acid gas involvements. The author is a leading researcher on the topics presented, and his development of gas-liquid flow pattern transition mechanism and multiphase flow models are major contributions to the multi-phase flow in wellbore. It focuses on acid gas and hydrate involvements, offering the latest results from drilling engineering computation research. This book presents an emerging hot spot in petroleum engineering, with more multi-phase flow methodologies developed and adopted to improve the engineering process for gas & oil drilling and production.